Performance in nonword repetition tasks among Mandarin-English bilingual children in Malaysia - Woon, Chai Ping; Yap, Ngee Thai; Lim, Hui Woan (Universiti Putra Malaysia Press, 2020)
The nonword repetition (NWR) task has been used to measure children’s expressive language skills, and it has been argued to have potential as an early language delay/ impairment detection tool as the NWR task can be conducted rather easily and quickly to obtain a quantitative as well as a qualitative measure of children’s attention to lexical and phonological information. This paper reports the performance of two NWR tasks among thirty bilingual Mandarin-English preschoolers between the age of four through six. The study indicated that performance in the NWR tasks showed a developmental trend with older children performing better than younger children. Word length also had a significant effect on performance, possibly an effect from better short-term memory capacity as the child grew older. The children also performed better in the Mandarin NWR task compared to the English NWR task. These findings suggest potential clinical applications for diagnosis of children with language impairment or at risk of language development delay. However, further studies should improve on the tasks to verify its efficacy and to obtain norms for performance with a larger sample of children at various age groups.